Biofunctional Inorganic Layered Double Hydroxide Nanohybrid Enhances Immunotherapeutic Effect on Atopic Dermatitis Treatment - Byun, Min Ji; Seo, Hee Seung; Lee, Joonghak; Ban, Kitae; Oh, Serim; Lee, Yun Young; Lim, Jaesung; Lee, Na Kyeong; Wang, Chi-Pin James; Kim, Minjeong; Han, Jun-Hyeok; Park, Juwon; et al. (Wiley - V C H Verlag GmbbH & Co., 2024)
Atopic dermatitis (AD) is a widespread, recurrent, and chronic inflammatory skin condition that imposes a major burden on patients. Conventional treatments, such as corticosteroids, are associated with various side effects, underscoring the need for innovative therapeutic approaches. In this study, the possibility of using indole-3-acetic acid-loaded layered double hydroxides (IAA-LDHs) is evaluated as a novel treatment for AD. IAA is an auxin-class plant hormone with antioxidant and anti-inflammatory effects. Following the synthesis of IAA-LDH nanohybrids, their ability to induce M2-like macrophage polarization in macrophages obtained from mouse bone marrow is assessed. The antioxidant activity of IAA-LDH is quantified by assessing the decrease in intracellular reactive oxygen species levels. The anti-inflammatory and anti-atopic characteristics of IAA-LDH are evaluated in a mouse model of AD by examining the cutaneous tissues, immunological organs, and cells. The findings suggest that IAA-LDH has great therapeutic potential as a candidate for AD treatment based on its in vitro and in vivo modulation of AD immunology, enhancement of macrophage polarization, and antioxidant activity. This inorganic drug delivery technology represents a promising new avenue for the development of safe and effective AD treatments. After synthesizing and administering IAA-LDH nanohybrids to an atopic dermatitis-mouse model, the nanohybrids induced M2-like macrophage polarization and reduced levels of ROS. Consequently, the IAA-LDH nanohybrids exhibited their anti-atopic properties (IAA; indole-3-acetic acid, IAA-LDH; IAA-loaded layered double hydroxides, ROS; reactive oxygen species).image